Concurrent Polycythemia Vera with Newly Diagnosed Multiple Myeloma: Case Report and Literature Review - Yuan J; Liu X; Wang Z; Li L; Wang F (Dove Medical Press, 2023)
Jing Yuan, Xuan Liu, Zhenzhen Wang, Liyuan Li, Fuxu Wang Department of Hematology, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050000, People's Republic of ChinaCorrespondence: Fuxu Wang, Department of Hematology, The Second Hospital of Hebei Medical University, 215 Heping West Road, Shijiazhuang, Hebei, 050000, People's Republic of China, Email cinderella8886@163.comAbstract: Concurrent polycythemia vera with newly diagnosed multiple myeloma is extremely rare. We described a 70-year-old woman with concurrent polycythemia vera and newly diagnosed multiple myeloma. Genetic testing confirmed the JAK2 V617F mutation for the first time, while determination of serum erythropoietin decreased. A retrospective review of our patient's case was conducted thereafter, and related literature was systemically reviewed. We totally identified eight cases with concurrent polycythemia vera with newly diagnosed multiple myeloma, which were further analyzed and compared. The present case is the first patient of newly diagnosed multiple myeloma with diagnosis of polycythemia vera confirmed by positive JAK2 V617F mutation. Abnormal erythremia, hepatosplenomegaly and thrombosis history suggested comorbidity of polycythemia vera with newly diagnosed multiple myeloma. The bortezomib-based chemotherapy regimen seemed to be effective on controlling the proliferation of erythrocyte. Whereas the pathogenesis of these two entities remains to be further investigated.Keywords: polycythemia vera, newly diagnosed multiple myeloma, concurrence, JAK2 V617F